Urinary Tract Infection in Idiopathic Nephrotic Syndrome in Children: Clinical Profile, Etiological Organisms and Antibiotic Sensitivity Patterns (Journal of Comilla Medical College Teachers' Association, 2025)
Background: Nephrotic syndrome is a common childhood renal disorder; the prevalence of Urinary tract infection (UTI) in these patients is high. The increased prevalence of UTI is due to immunoglobulin loss, defective T cell function, presence of ascites and relative malnutrition.Objective: To determine the clinical characteristics of UTI and its antimicrobial sensitivity pattern among the children with idiopathic nephrotic syndrome.Methods:  A cross-sectional study which was conducted among purposively selected 54 patients with idiopathic nephrotic syndrome in the department of pediatrics from January to June 2017 at Comilla Medical College Hospital. Data were collected by performing physical examination of the children and face-to-face interview of the parents and investigation reports using a structured questionnaire. Descriptive and bivariate analysis was done using the analytic software SPSS version 21.0. Means and standard deviations were calculated for parametric variables and means were compared using Student's t-test. Nonparametric variables were expressed in proportions. Differences between frequencies were tested using Chi-square test, p-values